2012
DOI: 10.1177/0021998312469240
|View full text |Cite
|
Sign up to set email alerts
|

Short beam interlaminar shear behavior and electrical resistance-based damage self-sensing of woven carbon/epoxy composite laminates in a cryogenic environment

Abstract: This article investigates the interlaminar shear behavior and damage detection of woven carbon fiber reinforced polymer composite laminates at cryogenic temperatures. Short beam shear tests were performed at room temperature and liquid hydrogen temperature (20 K), and the temperature dependence of the apparent interlaminar shear strength was examined. The electrical resistance of the composite specimens was also monitored during the tests. A detailed observation of the tested specimens was made to assess the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
2
14
2
Order By: Relevance
“…It is worth noting that the electrical resistance was actually slightly reduced with increased loading, which was due to the flexural deformation which involves partly compression of the specimen and a slightly reduced gap between CNTs within the network. This finding is consistent with other researches [16,35]. When interlaminar shear failure occurs, the network structure of the percolated CNTs is severely affected, leading to a dramatic change in sensing signals.…”
Section: Journal Of Nanomaterialssupporting
confidence: 93%
“…It is worth noting that the electrical resistance was actually slightly reduced with increased loading, which was due to the flexural deformation which involves partly compression of the specimen and a slightly reduced gap between CNTs within the network. This finding is consistent with other researches [16,35]. When interlaminar shear failure occurs, the network structure of the percolated CNTs is severely affected, leading to a dramatic change in sensing signals.…”
Section: Journal Of Nanomaterialssupporting
confidence: 93%
“…1,2 Among the most important development in materials in recent years are fiber reinforcement polymer (FRP) composite materials for structural applications such as automobile, aircraft, and sport goods have increased exponentially due to their mechanical properties to weight ratios, and their superior thermal and chemical performance as a comparison to conventional metal materials. 2,3 In addition, they can be used in fabrication of cryogenic storage tanks for liquid oxygen and hydrogen. 4 One of the unique features of FRP is that their properties can be tailored to meet different kinds of loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…25 Another study showed that cryogenic temperatures generally decreased the interlaminar strength of carbon/epoxy composites. 26 Wei and Zhang characterized the stitchinduced irregularities in fabric and composite structure using a fiber distortion model. 27 Zhao et al showed that z-stitching noticeably increases the impact damage tolerance of glass/polypropylene (PP) composites without an adverse effect on tensile properties.…”
Section: Introductionmentioning
confidence: 99%